4x+(x+3)+2(x+4)=

Simple and best practice solution for 4x+(x+3)+2(x+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+(x+3)+2(x+4)= equation:


Simplifying
4x + (x + 3) + 2(x + 4) = 0

Reorder the terms:
4x + (3 + x) + 2(x + 4) = 0

Remove parenthesis around (3 + x)
4x + 3 + x + 2(x + 4) = 0

Reorder the terms:
4x + 3 + x + 2(4 + x) = 0
4x + 3 + x + (4 * 2 + x * 2) = 0
4x + 3 + x + (8 + 2x) = 0

Reorder the terms:
3 + 8 + 4x + x + 2x = 0

Combine like terms: 3 + 8 = 11
11 + 4x + x + 2x = 0

Combine like terms: 4x + x = 5x
11 + 5x + 2x = 0

Combine like terms: 5x + 2x = 7x
11 + 7x = 0

Solving
11 + 7x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + 7x = 0 + -11

Combine like terms: 11 + -11 = 0
0 + 7x = 0 + -11
7x = 0 + -11

Combine like terms: 0 + -11 = -11
7x = -11

Divide each side by '7'.
x = -1.571428571

Simplifying
x = -1.571428571

See similar equations:

| ln(x)/ln(y) | | -4.8+7(1-3(25))=3(1-7(25)) | | (x-0.5)(x-0.5)+1.561=0 | | 2p^2x^2+pqx-15q^2=0 | | 5x-8=28-4x | | 5x-8=28-4 | | 56a(3+x-2b)=c(dx-2) | | x^4-6x^3+27x=0 | | (6n^4-2n+5n)+(2n+6n^4+4n^2)= | | .96+x=.16(12+x) | | 41x^2=9 | | B+x=18 | | 9x-8=5x+24 | | 2(x^3-5x^2+11x)=2x^3-5(2x^2+4x)+165 | | 15w-4(3w-1)=19 | | 15x-12=-12 | | 15x-12=-27 | | 4x+2x-42=-x-12+10x-6 | | N=323-192 | | 5x^2-13x=30 | | -8x/2 | | -7n+21=1-2n | | 4x+11y=4.6 | | X^2-12x=-72 | | 14-3(5t-12)=1-20+1 | | -4x+3(-2x+6)=8 | | 5x^2+2x+11= | | m+n+p=11 | | (y+3)+2y=(9y+6)-8 | | 5x+47=57 | | 5x(x-1)=2(1-x) | | -4(2w-1)=10-4w |

Equations solver categories